A hitchhiker's guide to the Trojan Horse Method. (April 2016) - Pizzone, R.G.; Spitaleri, C.; Cherubini, S.; D'Agata, G.; Guardo, G.L.; Gulino, M.; La Cognata, M.; Lamia, L.; Puglia, S.M.R.; Rapisarda, G.G.; Romano, S.; Sergi, M.L.; et al.
Abstract: Owing the presence of the Coulomb barrier at astrophysically relevant kinetic energies, it is very difficult, or sometimes impossible to measure astrophysical reaction rates in laboratory. This is why different indirect techniques are being used along with direct measurements. The THM is unique indirect technique allowing one measure astrophysical rearrangement reactions down to astrophysical relevant energies. The basic principle and a review of the main application of the Trojan Horse Method are presented. A step-by-step approach will be adopted in order to describe the features usually unknown to non-experts.